Root canal instrumentation of artificial primary teeth with rotary and reciprocating files: a micro-CT analysis - Chrisostomo, Daniela Alvim [UNESP]; Danelon, Marcelle; Furlan, Renan Diego; Duarte, Marco Antônio Hungaro; Mello-Moura, Anna Carolina Volpi; Duque, Cristiane (FapUNIFESP (SciELO), 2025)
This study compared the outcomes of two endodontic instrumentation protocols (rotary or reciprocating files), using artificial primary teeth and micro-computed tomography. Twenty-four artificial primary molars were equally distributed into two groups of 12, according to the type of instrumentation - rotary files (Sequence Baby NiTi Files©) or reciprocating files (X1-Blue File NiTi files©). The following parameters were evaluated: root canal and dentin volumes, canal transportation and centering ability, risk of root perforation, and time of instrumentation. Statistically significant differences between the two instrumentation protocols considering root canal transportation and centering ability were identified. There was no difference in dentin thickness, fractures, and cracks comparing preoperative and postoperative time points for both endodontic files. Although the time of instrumentation was shorter for reciprocating files, rotary files promoted smaller root canal enlargement. Instrumentation with reciprocating and rotary files proved generally safe for pulpectomy in primary molars, promoting a negligible reduction in dentin volume, canal transportation, and centering ability, thereby preserving dentin thickness and lowering the risk of fractures.